PERANCANGAN STRATEGI PENJUALAN FIXED BROADBAND PT X WILAYAH JAKARTA UTARA DENGAN METODE MATRIKS IE, SWOT, DAN AHP - Denastri Ginintiya Putri (2021)
PT X North Jakarta is the largest telecommunications company and internet network provider with one of its products, namely fixed broadband internet services. A large number of ODPs that are not connected to customers can cause losses for PT X. Therefore so that PT X does not suffer losses, the right sales strategy is needed so that fixed broadband sales can be optimal. This study aims to design a sales strategy based on the analysis of the company's internal and external factors. The methods used in this research are IFE and EFE matrices, IE matrix, SWOT, and AHP. The results of the IE matrix show that PT X is in cell V, namely hold and maintain. There are five alternative strategies based on the IE and SWOT matrix. In the AHP calculation, the main factor that plays a role in the fixed broadband sales strategy is the quality of fixed broadband, the main actor who plays a role is the Home Service division, and the main alternative strategy is optimizing digital marketing.